2012
DOI: 10.1007/s00167-012-2204-2
|View full text |Cite
|
Sign up to set email alerts
|

Returning to sports after surgical repair of acute proximal hamstring ruptures

Abstract: Case-control study, Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 25 publications
(36 reference statements)
3
38
0
2
Order By: Relevance
“…7,[27][28][29]41 In the present study, 18 (58%) of the patients reported that they had regained preinjury activity level at a mean of 9 months (range, 3-18 months and Cohen et al 13 reported concerns of reinjury as one of the reasons why the patients did not return to all preinjury activities after surgical repair of proximal total hamstring rupture.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…7,[27][28][29]41 In the present study, 18 (58%) of the patients reported that they had regained preinjury activity level at a mean of 9 months (range, 3-18 months and Cohen et al 13 reported concerns of reinjury as one of the reasons why the patients did not return to all preinjury activities after surgical repair of proximal total hamstring rupture.…”
Section: Discussionmentioning
confidence: 44%
“…13,14,26,36 Return to preinjury level of sport and patient satisfaction are usually used as main outcomes after undergoing repair of proximal hamstring tendon rupture. 9,28,37,41 Isokinetic muscle strength has been used as a performance-based outcome, showing a mean limb symmetry index (LSI) between 80% and 95%, although most of the studies have included few patients. 9,18,27,36 Only 2 previous studies have assessed performance-based outcomes after surgical treatment in a larger population (n > 20).…”
Section: Introductionmentioning
confidence: 99%
“…Sallay et al 14 and Rust et al 12 described immobilization of the knee at 90° for 4 to 6 weeks. Lefevre et al 9 , 10 and Chahal et al 4 described immobilization of the knee at 30° for 6 weeks. Mansour et al 11 described using a hinged knee brace to limit extension for a minimum of 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…It occurs mainly as a result of soft tissue avulsion alone or with a bone fragment detached from the ischial tuberosity, at the proximal tip of the muscle, but is considered to be very rare [20]. When this type of injury occurs to a soccer player he may often need surgical intervention [4,[21][22][23]. Magnetic resonance imaging or sonography will aid in the diagnosis of the scope of damage caused.…”
Section: Degree Of Damage Causedmentioning
confidence: 99%